Exploring Consumer Emotional Relationships through Brand Experience to Enhance Satisfaction in Fashion: Gender and Age Perspectives - Marsasi, Endy Gunanto; Barqiah, Sarah; Nafisyah, Ulin (Universitas Brawijaya, Indonesia, 2025)
The fashion industry faces challenges in building strong emotional relationships with consumers amidst increasingly fierce market competition, especially with differences in preferences based on gender and age. This study aims to explore the influence of brand experience on brand love, brand equity, and brand authenticity, and how these factors affect consumer satisfaction. The theory in this study uses the Relationship Theory approach. This study analyzes the emotional relationship between consumers and brands in the fashion industry. Data were collected through a survey of 419 respondents from Generations Y and Z using purposive sampling, and analyzed using Structural Equation Modeling (SEM). The results of the study indicate that brand experience significantly affects brand love, brand equity, and brand authenticity, but the relationship between brand authenticity and consumer satisfaction is not significant. In contrast, brand love and brand equity show a positive influence on consumer satisfaction. Multigroup analysis shows that women tend to have stronger emotional relationships with brands than men, while older consumers emphasize the importance of brand equity to their satisfaction. This study provides important insights into marketing strategies through brand experience, brand love, and authenticity to increase consumer satisfaction, while filling the literature gap related to the dynamics of consumer emotional relationships with fashion brands from a gender and age perspective.